2017
DOI: 10.1186/s13031-017-0111-3
|View full text |Cite
|
Sign up to set email alerts
|

Low levels of viral suppression among refugees and host nationals accessing antiretroviral therapy in a Kenyan refugee camp

Abstract: BackgroundRefugees and host nationals who accessed antiretroviral therapy (ART) in a remote refugee camp in Kakuma, Kenya (2011–2013) were compared on outcome measures that included viral suppression and adherence to ART.MethodsThis study used a repeated cross-sectional design (Round One and Round Two). All adults (≥18 years) receiving care from the refugee camp clinic and taking antiretroviral therapy (ART) for ≥30 days were invited to participate. Adherence was measured by self-report and monthly pharmacy re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Provide ART to patients [43][44][45][46][47] A proper assessment of current and near-future available resources; clinical HIV severity assessment by WHO staging; ART triage by clinical severity if there is a scarcity of supply; increase links to care of identified people with HIV by creating communication means adapted to personal preferences, including by providing mobile phones; setup of multidisciplinary mobile teams for ART provision with doctors, nurses, psychological health-care providers, social workers, and peer-to-peer support, equipped with point-of-care molecular tests (eg, PCR for HIV viral load, hepatitis, and tuberculosis), and emergency HIV care in displaced communities or people stuck in warfare, and operating within the existing mobile teams network of the Alliance of Public Health; health-care providers available with experience prescribing ART or with access to a professional HIV network or guidelines; facilitate the integration of people with HIV into health-care systems in host countries and facilitate resource availability (ie, medication, foremost dolutegravir-based regimens including TLD)…”
Section: Art Coveragementioning
confidence: 99%
See 3 more Smart Citations
“…Provide ART to patients [43][44][45][46][47] A proper assessment of current and near-future available resources; clinical HIV severity assessment by WHO staging; ART triage by clinical severity if there is a scarcity of supply; increase links to care of identified people with HIV by creating communication means adapted to personal preferences, including by providing mobile phones; setup of multidisciplinary mobile teams for ART provision with doctors, nurses, psychological health-care providers, social workers, and peer-to-peer support, equipped with point-of-care molecular tests (eg, PCR for HIV viral load, hepatitis, and tuberculosis), and emergency HIV care in displaced communities or people stuck in warfare, and operating within the existing mobile teams network of the Alliance of Public Health; health-care providers available with experience prescribing ART or with access to a professional HIV network or guidelines; facilitate the integration of people with HIV into health-care systems in host countries and facilitate resource availability (ie, medication, foremost dolutegravir-based regimens including TLD)…”
Section: Art Coveragementioning
confidence: 99%
“…Provide ART antenatally, perinatally, and postnatally 25,26 Identify and link patients to care; health-care providers experienced in HIV obstetric care and vertical transmission prevention with access to a professional HIV network or guidelines Management of AIDS Establish swift, safe, and targeted logistics for medication (eg, cotrimoxazole; and rifampicin, isoniazid, pyrazinamide, and ethambutol) 35,24 Solid communication lines within, and support of, professional HIV networks (eg, online consultation for complex cases); use of professional HIV networks and associated support initiatives for expertise and infrastructure (eg, EACS's aware.hiv Ukraine initiative, 36 and ECEE's ART for Ukrainians abroad initiative 37 ); proper assessment of current and near-future available resources; medication triage by clinical severity if there is a scarcity of medication Free access to health-care services to help in the early detection of opportunistic infections 24,26 Resources (clinics and medication) available; appropriate liberal governmental health-care regulations and swift policy implementation Identify patients in need and allocation of AIDS medication 46 Registration of patients with AIDS; identifying AIDS by clinical assessment; health-care providers available with experience in managing AIDS or with access to a professional HIV network or guidelines…”
Section: Prevent Vertical Transmissionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, viral suppression was significantly higher in citizens (73%) than migrants (66%); a study in Kenya found similar, unacceptably low viral suppression rates in refugees and host nationals (74% and 70%; P = .66). [33]…”
Section: Discussionmentioning
confidence: 99%